2018
DOI: 10.1021/acsami.8b01175
|View full text |Cite
|
Sign up to set email alerts
|

Small Titanium-Based MOFs Prepared with the Introduction of Tetraethyl Orthosilicate and Their Potential for Use in Drug Delivery

Abstract: Metal-organic frameworks (MOFs) have attracted much attention in the areas of biomedicine and medicine owing to their versatile porous structure. However, the oversize and high cellular toxicity of some metal-based MOF particles have hindered their development. Therefore, a series of small Ti-based MOFs are prepared with the introduction of tetraethyl orthosilicate (TEOS) into the reaction system. Compared with the Ti-based MOFs prepared by traditional methods, the size of the Ti-based MOFs prepared with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…Tailoring of the pore size (with tetraethyl orthosilicate-modified MIL-125-NH 2 ) has been demonstrated to be highly effective for drug delivery, especially in the case of IBU release. 40 Moreover, on the basis of the surface area, TC-Zr-DASDCA also showed increased adsorption or loading of IBU compared with pristine Zr-DASDCA (Figure 3b). The competitive loading of IBU onto TC-Zr-DASDCA might also be explained by reduced pore size.…”
Section: Resultsmentioning
confidence: 97%
“…Tailoring of the pore size (with tetraethyl orthosilicate-modified MIL-125-NH 2 ) has been demonstrated to be highly effective for drug delivery, especially in the case of IBU release. 40 Moreover, on the basis of the surface area, TC-Zr-DASDCA also showed increased adsorption or loading of IBU compared with pristine Zr-DASDCA (Figure 3b). The competitive loading of IBU onto TC-Zr-DASDCA might also be explained by reduced pore size.…”
Section: Resultsmentioning
confidence: 97%
“…Recently metal-organic frameworks (MOFs), porous materials of a crystalline structure comprising bridged organic ligands and metal centers, have been attracted significant attention in gas sorption average owing to their large pore volumes and surface areas. Several studies have been 1 3 reported on MOFs utilization as heterogeneous catalysts [1][2][3][4], in gas storage [5], separation [6], drug delivery [7], and sensing [8,9]. These materials have been explored because of their intrinsic high surface area, tunable pores, and various functionalities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐organic frameworks (MOFs) are a new type of organic‐inorganic hybrid materials and have been attracted much attention 25‐28 . In recent years, MOFs had been explored as a novel flame retardant for polymers.…”
Section: Introductionmentioning
confidence: 99%